IMPLICATURE ANALYSIS ON CIGARETTE ADVERTISEMENT SLOGANS - ., MUTMAINNAH (Jurnal Ilmiah Mahasiswa FIB, 2014)
Mutmainnah. 2013. Implicature Analysis on Cigarette Advertisement Slogans. Study Program of English, Department of Languages and Literature, Faculty of Cultural Studies,  Universitas  Brawijaya. Supervisor:  Endang  Sasanti; Co-supervisor: Istiqomah Wulandari.  Kata Kunci: Implicature, cigarette advertisement slogans.  Some advertisements cannot show the products to persuade people because the government forbids the advertisement to show or mention the objects of the products. In Indonesia there are three products which have to conform with this regulation, they are alcohol, condom, and cigarette. So, this makes the companies create the slogans of the products more creative than others. Therefore, they are interesting to be used as data for this research because they have a lot of implicit meanings. In this study, the problem of the study proposed is what are the intended meanings behind the cigarette advertisement slogans?. This research uses Grice’s conversational implicature  theory to conduct the research. This study uses qualitative approach in relation to the use of clear and systematic description about the phenomena being studied. Descriptive study in textual analysis is applied in this study to analyze  the cigarette advertisement slogans. The data are downloaded from the internet and selected from ten cigarette advertisements that appear on television most frequently. The collected data are then analyzed in terms of the message conveyed in the generalized and particularized implicature of cigarette advertisement slogans. In this research, the researcher found all  generalized and particularized implicature of the data. The researcher also found most of the intended meanings of the cigarette slogans contain  persuasion words to attract the consumers, a message for people or the consumers, and also an encouragement word. Also there are some companies trying to give information for the consumers that the products are changed such as in the size or the taste. In conclusion, all the cigarette companies have different styles of making the slogans to attract the consumers to buy the products. The researcher suggests the next researchers who want to conduct a similar research to understand more  about  implicature,  not only in conversational implicature but also in conventional implicature and flouting maxim, they can also use another theory to make the study more complete like Relevance Theory by Sperber and Wilson. It is expected  that their study can  be more  complete  and understandable.